2005
DOI: 10.1172/jci200522452
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of WNK1 and WNK4 interaction in the regulation of thiazide-sensitive NaCl cotransport

Abstract: With-no-lysine (WNK) kinases are highly expressed along the mammalian distal nephron. Mutations in either WNK1 or WNK4 cause familial hyperkalemic hypertension (FHHt), suggesting that the protein products converge on a final common pathway. We showed previously that WNK4 downregulates thiazide-sensitive NaCl cotransporter (NCC) activity, an effect suppressed by WNK1. Here we investigated the mechanisms by which WNK1 and WNK4 interact to regulate ion transport. We report that WNK1 suppresses the WNK4 effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
117
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 22 publications
5
117
2
Order By: Relevance
“…Long WNK1 physically interacts with WNK4 (35), which also stimulates endocytosis of ROMK (11). Thus, it is interesting to know whether WNK1 regulates ROMK1 synergistically with WNK4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long WNK1 physically interacts with WNK4 (35), which also stimulates endocytosis of ROMK (11). Thus, it is interesting to know whether WNK1 regulates ROMK1 synergistically with WNK4.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activation of ENaC by WNK1 requires the N-terminal amino acids 1-220 (15). Also, release of WNK4-mediated inhibition of Na-Cl cotransporter by WNK1 requires the kinase domain of WNK1 (35). Thus, it appears that hypertension in PHA II patients with WNK1 mutation is likely also caused by an increase in long WNK1, not KS-WNK1.…”
Section: Discussionmentioning
confidence: 99%
“…T he WNK family of serine͞threonine kinases has been shown to function as important regulators of salt homeostasis (1)(2)(3)(4)(5)(6)(7)(8)(9). Mutations in the WNK4 or WNK1 genes cause a familial disorder [pseudohypoaldosteronism type II, (PHAII)] of diminished renal potassium excretion, excessive sodium retention, and hypertension (10).…”
mentioning
confidence: 99%
“…Our observation after immunofluorescence staining showed that normally NCC was mainly distributed on the Cos-7 cell membrane, with a small amount distributed in the cytoplasm ( Figure S2 in Supporting Information). WNK3 could increase the expression of NCC both on the membrane and in the cytoplasm of mammalian cells.Previous studies have indicated the amino terminal of WNK4 is the critical region in the regulation of NCC (Yang et al, 2005). Our present study found WNK3 (421-1800) fragment without the kinase domain had no effect on NCC at all while wild type WNK3 and WNK3 (1-420) fragment, containing the kinase domain, could increase NCC expression obviously.…”
mentioning
confidence: 40%
“…Previous studies have indicated the amino terminal of WNK4 is the critical region in the regulation of NCC (Yang et al, 2005). Our present study found WNK3 (421-1800) fragment without the kinase domain had no effect on NCC at all while wild type WNK3 and WNK3 (1-420) fragment, containing the kinase domain, could increase NCC expression obviously.…”
mentioning
confidence: 40%